The rise of traditional African religion in post-apartheid South Africa - Denis, Philippe (Missionalia, 2006)
The paper discusses the state of traditional African religion in post-apartheid South Africa. It argues that since the coming of democracy this form of religion has occupied a more important position in civil society than ever before. The new political situation has created a context that is eminently favourable to the expansion of traditional African religion. This happens in several ways. First, as an essential element of indigenous knowledge systems, it is recognised as a field of scientific research. Second, various steps are taken, among health practitioners and in Parliament, to give traditional healers formal recognition. Third, in the Christian churches more and more theologians openly advocate a dialogue with African traditional religion. Fourth, in various parts of the country, in KwaZulu-Natal and in the Eastern Cape in particular, groups of women vigorously promote the renewal of virginity testing, as a way of combating the spread of HIV / AIDS. In the new South Africa, African traditional religion has become more visible, but it is also changing. To gain recognition it has to fulfil a variety of new legal, social and cultural requirements.
free
Keywords: Culture and religion; Folk religion; African; Healers; South Africa – Religion; South Africa.; Virginity – Religious aspects – African religion